New insights into the genome and transmission of the microsporidian pathogen Nosema muscidifuracis - Xiong, Xiao; Geden, Christopher J.; Bergstralh, Dan T.; White, Roxie L.; Werren, John H.; Wang, Xu (Frontiers in Microbiology, 2023)
Nosema is a diverse genus of unicellular microsporidian parasites of insects and other arthropods. Nosema muscidifuracis infects parasitoid wasp species of Muscidifurax zaraptor and M. raptor (Hymenoptera: Pteromalidae), causing ~50% reduction in longevity and ~90% reduction in fecundity. Here, we report the first assembly of the N. muscidifuracis genome (14,397,169 bp in 28 contigs) of high continuity (contig N50 544.3 Kb) and completeness (BUSCO score 97.0%). A total of 2,782 protein-coding genes were annotated, with 66.2% of the genes having two copies and 24.0% of genes having three copies. These duplicated genes are highly similar, with a sequence identity of 99.3%. The complex pattern suggests extensive gene duplications and rearrangements across the genome. We annotated 57 rDNA loci, which are highly GC-rich (37%) in a GC-poor genome (25% genome average). Nosema-specific qPCR primer sets were designed based on 18S rDNA annotation as a diagnostic tool to determine its titer in host samples. We discovered high Nosema titers in Nosema-cured M. raptor and M. zaraptor using heat treatment in 2017 and 2019, suggesting that the remedy did not completely eliminate the Nosema infection. Cytogenetic analyses revealed heavy infections of N. muscidifuracis within the ovaries of M. raptor and M. zaraptor, consistent with the titer determined by qPCR and suggesting a heritable component of infection and per ovum vertical transmission. The parasitoids-Nosema system is laboratory tractable and, therefore, can serve as a model to inform future genome manipulations of Nosema-host system for investigations of Nosemosis.